Qualidade dos alimentos monitorados pelo PROGVISA/MG no período de 2007 a 2013 - Gesiane Peroni Brandão de Almeida (2015)
The Sanitary Surveillance of State of Minas Gerais, conducts the State Food Quality Monitoring Program (PROGVISA) annually since 2003. In this program, foods from the retail market are collected and analyzed. This study aimed to critically analyze the reports generated from 2007 to 2013. 7,746 reports of samples distributed in 21 categories and 83 types of food were analyzed. The total number of unsatisfactory reports were 6,210 (80.2%), with 4,193 (67.5%) of them related to labeling and 2,017 (32.5%) to labeling and/or other parameters. Out of the total samples analyzed, the percentage with labeling problems independent of other analysis, was 79.3% and only 0.8% had other problems rather than labeling. The percentage of unsatisfactory reports by category was: 100% for sugar, food for enteral nutrition; food with functional and or health claims; and honey; 70-99% for food for athletes, candies, chocolates; beverages; coffee, barley, tea, yerba mate and soluble products; chocolate and cocoa products; spices, seasonings and sauces; ices; milk and milk products; meat products; products of cereals; proteinaceous products of vegetable origin; vegetable products (other than palm hearts), produce of fruits and edible mushrooms; palm hearts; and mixes for food preparation and food ready for consumption. In the other categories, unsatisfactory reports were less than 69%. Data were also analyzed in terms of the reasons that led to the rejection by food type per year and unsatisfactory analysis, for labeling as well as for microbiological, physico-chemical and macro and microscopic